(untitled) (Comparative & International Education Series, 2021)
Chapter 1|12 pages Reimagining the Field: International Students in American Community Colleges By Gregory F. Malveaux, Krishna Bista American community colleges are prestigious global institutions of higher education with about 13 million students studying in a wide range of programs and disciplines. These colleges are highly sought after; offering low-cost, workforce-based college instruction. American community colleges support and prepare nontraditional students, including students of color, veterans, international students, low socio-economic status students, parent-students, individuals with circumstances that prevent them from attending four-year institutions, and those who have chosen to forgo attending four-year colleges and universities in a globally competitive world. There are nearly 97,000 international students who pursue their education at community colleges. This chapter outlines international student trends and these students’ experiences at American community colleges. It also reports general impacts of international students who largely contribute to campus diversity, internationalization initiatives, and national revenues in the United States.